DEVELOPING ENGLISH LANGUAGE SKILLS IN EARLY CHILDHOOD THROUGH THE CHORAL SPEAKING METHOD AT TABIKA KEMASH NUR AISYAH - Annisa Pradita; Hisra, Mutia Peorita; Nayata Putri Pujiati; Siti Nabiilah Syazlika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to enhance early childhood English proficiency through the implementation of the Choral Speaking method combined with a bilingual approach. Early childhood is a critical period for language acquisition; however, many preschool learners demonstrate limited English comprehension, which affects their motivation and participation. This study employed a qualitative approach using participatory observation and in-depth interviews. The program was conducted at Tabika Kemas Nur Aisyah using the Curriculum Standard Prasekolah Kebangsaan (CSPK) with a balanced bilingual approach (50% Malay and 50% English). The Choral Speaking method was implemented as a structured group-based activity emphasizing repetition, rhythm, and pronunciation practice. The findings indicate that children demonstrated increased enthusiasm, improved vocabulary acquisition, and more accurate pronunciation. In addition, children showed greater confidence in using English. This study highlights that interactive group-based methods integrated with bilingual instruction effectively support early childhood English learning.